Persepsi Siswa Terhadap Keteladanan Guru Pendidikan Agama Kristen Pada Sekolah Menengah Atas Negeri Di Malinau - Septiani A.; Eirene Mary (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
Exemplary is a person's attitude in setting an example through good actions so that they can be role models for other. Christian Education (CE) teacher must be role models for students as well as for the community to be able to apply in daily life what is taught in classroom through words, behavior, love, faithfulness, and purity of life.Â In addition, CE teacher must meet the personality competencies of teachers, namely: they must be patient, honest, disciplined and fair. The formulation of the problem in this study is how students perceive the example of CE teachers.Â The purpose of the study was to describe students' perceptions of the example of CE teachers. The research method used in this study is a qualitative research method.Â From the results of the study, it was concluded that based on student perceptions, CE teacher have become role models in several ways and have not become role models for several other things.